Dose-intensive chemotherapy including rituximab is highly effective but toxic in human immunodeficiency virus-infected patients with Burkitt lymphoma/leukemia: parallel study of 81 patients. Issue 10 (October 2014) - Xicoy, Blanca; Ribera, Josep-Maria; Müller, Markus; García, Olga; Hoffmann, Christian; Oriol, Albert; Hentrich, Marcus; Grande, Carlos; Wasmuth, Jan-Christian; Esteve, Jordi; van Lunzen, Jan; del Potro, Eloy; et al.
Abstract The results of intensive immunochemotherapy were analyzed in human immunodeficiency virus (HIV)-related Burkitt lymphoma/leukemia (BLL) in two cohorts (Spain and Germany). Alternating cycles of chemotherapy were administered, with dose reductions for patients over 55 years. Eighty percent of patients achieved remission, 11% died during induction, 9% failed and 7% died in remission. Four-year overall survival (OS) and progression-free survival (PFS) probabilities were 72% (95% confidence interval [CI]: 62–82%) and 71% (95% CI: 61–81%). CD4 T-cell count < 200/μL and bone marrow involvement were associated with poor OS (hazard ratio [HR] 3.2 [1.2–8.3] and HR 2.7 [1.1–6.6]) and PFS (HR 3.5 [1.3–9.1] and HR 2.4 [1–5.7]), bone marrow involvement with poor disease-free survival (DFS) (HR 14.4 [1.7–119.7] and Eastern Cooperative Oncology Group (ECOG) score > 2 (odds ratio [OR] 11.9 [1.4–99.9]) with induction death. In HIV-related BLL, intensive immunochemotherapy was feasible and effective, but toxic. Prognostic factors were performance status, CD4 T-cell count and bone marrow involvement.